Evaluating the Use of Serum Inflammatory Markers for Preoperative Diagnosis of Infection in Patients with Nonunions. (10th October 2017) - Wang, Song; Yin, Peng; Quan, Chenliang; Khan, Kamran; Wang, Guoqi; Wang, Lijuan; Cui, Lin; Zhang, Licheng; Zhang, Lihai; Tang, Peifu
Abstract : Purpose . The aim of this study is to evaluate the effectiveness of laboratory serum tests in the diagnosis of infected nonunion. Methods . Forty-two patients suspected of having infected nonunion were investigated in the study. The serum levels of white blood-cell count (WBC), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and interleukin-6 (IL-6) were measured. A positive diagnosis of infection was made on the basis of the positive culture results. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of each test were calculated. Results . The sensitivity and specificity of CRP both were higher than IL-6: 60.0% versus 57.1% and 85.7% versus 57.1%, respectively. With one, two, three, and four positive tests, the predicted probabilities of infection were 66.7%, 90.9%, 100%, and 100%, respectively, but the number of patients who had three or four positive tests was small. Conclusions . The diagnostic utility of IL-6 is inferior to CRP and the finding conflicts with previous conclusions drawn from periprosthetic infections. Laboratory analysis of serum inflammatory markers alone is not an effective screening tool for patients suspected of having an infected nonunion.